The Influence of the Number of Taxpayers, Investment, and Gross Regional Domestic Product (GRDP) on Final Income Tax Revenue from MSMEs in North Sulawesi - Fitriyanti Natalia Sambur; Joseph Philip Kambey; Andrew Patrick Marunduh (CV Edujavare Publishing, 2026)
The purpose of this study is to assess the effect of the Number of Taxpayers Who Pay, Investment, and Gross Regional Domestic Product (GRDP) on the Final Income Tax Revenue of SMEs in North Sulawesi for the period 2022–2024. A quantitative method was employed, with all districts and cities in North Sulawesi Province considered as the population. From this population, all 15 districts and cities were selected as the sample using the saturated sampling method, resulting in a total of 45 observations. The analysis was conducted using panel data regression with the Random Effect Model (REM) as the selected model, and data processing was carried out using EViews 12 software. The results indicate that the Number of Taxpayers Who Pay has a significant effect on the Final Income Tax Revenue of SMEs. Investment has a significant effect on the Final Income Tax Revenue of SMEs. GRDP has a significant effect on the Final Income Tax Revenue of SMEs. The simultaneous test shows that all three variables collectively have a significant effect on the Final Income Tax Revenue of SMEs. The correlation coefficient value of 54.41% indicates that the strength of the relationship between the independent and dependent variables falls into the moderate to strong category. The coefficient of determination shows that approximately 51.12% of the variation in the Final Income Tax Revenue of SMEs can be explained by the Number of Taxpayers Who Pay, Investment, and GRDP, while the remaining 48.88% is explained by other factors not examined in this study